PERENCANAANSTRATEGIKSEKOLAH DALAM PENGEMBANGAN PENDIDlKAN BERBASIS LUAS BERORIENTASI KECAKAPAN HIDUP DI SMK - Wiyono, Giri; Sunarto, Sunaryo (Universitas Negeri Yogyakarta, 2004)
The purpose of this IPTEKS application program is to increase school headmasters' ability for making the schoolwork programs based strategic planning process. Therefore headmasters of Vocational Hig School (SMK) have: (1) the ability to conduct the school needs analysis, (2 the ability to formulate the school vision and mission, (3) the ability to draw up plans for school development, (4) the ability to perform SWOT analysi (internal and external condition), (5) the ability to formulate the schoo objective, (6) the ability to understand of the way to formulate strategy.Methods used in Strategic Planning Workshop are lecture, questionanswer, demonstration, group-task, seminar; guidance to make th schoolwork programs based a strategic planning process, and games i outbound training. Learning approaches used in this training are adul education and practice.The result of Strategic Planning Workshop can be concluded afollows: (a) Participants have global vision in technology and strategic issues of education as formulation and development process of th schoolwork programs for increasing quality of education in each school. (b Participants can formulate and develop the schoolwork programs based o strategic planning process oriented for school needs in the field of life skills (c) Participants can develop self-power as headmasters who have th transformational leadership to implement the schoolwork programs based ostrategic planning and can control the operation of this program interatedly.Key words: strategic planning, life skill